A review on anode on-cell catalyst reforming layer for direct methane solid oxide fuel cells. (16th July 2021) - Qiu, Peng; Sun, Shichen; Yang, Xin; Chen, Fanglin; Xiong, Chunyan; Jia, Lichao; Li, Jian
Abstract: The commercialization of solid oxide fuel cells (SOFCs) can be significantly promoted with the direct utilization of methane, which is the primary component in natural gas and the second most abundant anthropogenic greenhouse gas. However, carbon deposition on most commonly used Ni-based anode is the bottle-necking issue inhibiting long-term stability of direct methane SOFCs. To avoid such a problem, methane is typically reformed (internally or externally) in SOFCs. Considering the cost, system simplification, coking resistance, and material selection, the on-cell catalytic reforming layer (OCRL) is one of the most promising designs for direct methane SOFCs. Reforming catalytic materials are typically consisted of active component, substrate and catalytic promoter, all of which have a significant impact on the catalytic activity, sintering resistance and coking resistance of methane reforming catalysts. This review summarizes the influence of the various components, some common OCRL materials and their applications in direct methane SOFCs, reforming and coking resistance mechanism, as well as the remaining challenges. The effective utilization of OCRL plays a pivotal role in promoting the development of direct methane SOFCs and the commercialization of SOFCs. Highlights: Recent progress of on-cell catalytic reforming layer for SOFC is presented. Influence of composition on the properties of the reforming catalyst is summarized. Challenges and prospects of on-cell catalytic reforming layer in SOFCs are provided.